Effect of Inhaled Oil Aromatherapy on Emesis Gravidarum in First Trimester Pregnant Women - Ririn Anggraini; Melia Rahma; Yuli Andari (JURNAL KEBIDANAN KESTRA (JKK), 2022)
Emesis Gravidarum (nausea and vomiting) is a common complaint in early pregnancy due to increased production of the hormones estrogen, progesterone, and placental human chorionic gonadotrophs. Peppermint aromatherapy is a therapeutic measure to treat emesis gravidarum in pregnant women. This aromatherapy has a cool, refreshing, and makes you feel comfortable. This study aims to find out how to give inhaled peppermint oil aromatherapy that can affect emesis gravidarum in first trimester pregnant women. The research method used is a literature study where an analysis of journals and articles with a review of existing theories is carried out.The journals that have been reviewed are as many as 16 journals. The results of this study revealed that the content of peppermint that can overcome emesis gravidarum is methhol and methone. The amount of peppermint is given 2-3 drops of peppermint essential oil on a tissue with a distance of 3-5 cm and inhaled for 5-10 minutes by doing 2 times a day in the morning and evening. From the results of the study that there are differences in the effectiveness of peppermint aromatherapy with other aromatherapy, where peppermint oil aromatherapy is more effective in overcoming nausea and vomiting in first trimester pregnant women. Health workers, especially midwives, can provide peppermint aromatherapy care to reduce emesis gravidarum in first trimester pregnant women.